The macroeconomics of a financial Dutch disease - Alberto Botta (Levy Economics Institute of Bard College, 2015)
We describe the medium-run macroeconomic effects and long-run development consequences of a financial Dutch disease that may take place in a small developing country with abundant natural resources. The first move is in financial markets. An initial surge in foreign direct investment targeting natural resources sets in motion a perverse cycle between exchange rate appreciation and mounting short- and medium-term capital flows. Such a spiral easily leads to exchange rate volatility, capital reversals, and sharp macroeconomic instability. In the long run, macroeconomic instability and overdependence on natural resource exports dampen the development of nontraditional tradable goods sectors and curtail labor productivity dynamics. We advise the introduction of constraints to short- and medium-term capital flows to tame exchange rate/capital flows boom-and-bust cycles. We support the implementation of a developmentalist monetary policy targeting competitive nominal and real exchange rates in order to encourage product and export diversification.
Keywords: F32; O14; O24; 330; Financial Dutch Disease; Exchange Rate Volatility; Macroeconomic Instability; Developmentalist Monetary Policy